GEOINFORMATION DATABASE OF DRINKING UNDERGROUND WATER’S CHEMICAL COMPOSITION FOR KYIV’S TERRITORY - KOSHLIAKOV, O.; KOSHLIAKOVA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geoinformation database model of chemical composition for underground water used as potable water source of Kyiv is proposed. Structure of attributive table, contains chemical composition quantities and bacteriological quality measures, is developed. The table will contain available data from the end of XIX century to the present. It allows to make the efficient estimation of water quality spatiotemporal changes as provided by active in Ukraine hygienic and ecological charges (The national standart of Ukraine 4808:2007).